2021
DOI: 10.1002/aisy.202000221
|View full text |Cite
|
Sign up to set email alerts
|

High‐Displacement, Fiber‐Reinforced Shape Memory Alloy Soft Actuator with Integrated Sensors and Its Equivalent Network Model

Abstract: For soft robotics, shape memory alloy (SMA)‐based elastomeric actuators are a promising material combination but their maximum stroke is limited by the small inherent contraction of SMAs. In this work, a textile‐reinforced soft actuator is presented, which has additional SMA wire length included in the textile structure as well as a sensoric textile to track the actuator's pose. This strategy eliminates the need for external SMA wires with extra mechanical components. Various experiments with different excitat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 26 publications
(22 reference statements)
0
15
0
Order By: Relevance
“…When 10 % strain was reached, it was kept constant for 30 s in order to evaluate the relaxation behavior. 10 % maximum strain were chosen because that is a sufficient strain level for many applications even for soft actuators with a bending angle over 180 ° [5].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…When 10 % strain was reached, it was kept constant for 30 s in order to evaluate the relaxation behavior. 10 % maximum strain were chosen because that is a sufficient strain level for many applications even for soft actuators with a bending angle over 180 ° [5].…”
Section: Methodsmentioning
confidence: 99%
“…have shown for soft robotic applications, the combination of fibers with an elastomer matrix can be advantageous [3,4]. In the textile the sensors can be integrated along with fibershaped actuators and reinforcement yarns to achieve robust, yet highly flexible structures [5].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Han et al developed an SMA-based textile morphing flower that blooms under an electric current and confirmed its various modes of deformation [ 32 ]. Mersch et al presented an SMA-based integrated soft sensor–actuator system with a bending angle of 270° [ 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…Results showed that by extending the hinged width of AHFRP by two and three times from the hinged width of 40 mm, the maximum deformation was raised to 42.7 % and 64.6 %, respectively. Mersch et al [48] created SMA-based elastomeric actuators which were able to achieve a bending angle of 270 • at a power input of 18 W. Araújo et al [49] manufactured carbon-fibre-reinforced polymers (CFRP) integrated with NiTi SMA wire actuators in a single direction. The samples exhibited standard thermal buckling behaviour, which caused the beam specimen's tip deflection to increase as the temperature rose to 100 • C. A bigger and more stable decrease in thermal buckling was found in CFRP integrated with SMA wires.…”
Section: Introductionmentioning
confidence: 99%